Gambling to Leapfrog in Status? - Tim Friehe; Mario Mechtel (Center for Economic Studies and ifo Institute (CESifo), 2013)
This paper shows that households with positional concerns and convex status utility use gambling to attempt leapfrogging in the social hierarchy. We test this theoretical prediction relying on household data that is representative for Germany, proxying the status orientation of households by their expenditures for conspicuous consumption. Our empirical results strongly indicate that households who care about status are more likely to participate in gambling and invest more in gambling, while they save less. In addition, results regarding socio-economic and demographic characteristics are reported. For example, we find that households in East Germany are less likely to gamble and expend smaller amounts on gambling.
Keywords: D12; D14; D62; 330; conspicuous consumption; status-seeking; relative income; gambling behavior; behavioral economics